Community Behavior in Waste Disposal Along the Banks of the Durian River, Namaelo Subdistrict, Masohi City, Central Maluku Regency - Suatrat, Andhyagis; Sihasale, Daniel Anthoni; Lasaiba, Mohammad Amin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2024)
This study explores the issue of waste disposal along the banks of the Durian River in Masohi City, Maluku, and analyzes the factors influencing community behaviour related to the river. With a descriptive qualitative approach, the research highlights the need for more awareness and concern among the community and the insufficient government response to the issue—the study through observations, interviews, and documentation. The results indicate that addressing the waste disposal problem along the Durian River in Masohi City requires collaboration and concrete actions. The government needs to enforce strict policies and impose firm penalties for violations. Relevant institutions should actively monitor the river, implement regular cleanup programs, and support community initiatives. Public education, the development of controlled facilities, and recycling are critical factors in waste management. The environment along the Durian River can become clean and sustainable by monitoring waste management programs and fostering cooperation between the government, institutions, and the community. Concrete measures, such as penalties, cleanup programs, and education, must be carried out collectively to change community behaviour and culture.